A motif-index of traditional Polynesian narratives - Kirtley, Bacil F., 1924- (University of Hawaii Press, 1971)
"This ... work analyzes and classifies the story themes of Polynesian myths, tales and legends according to an internationally employed system developed by Stith Thompson in his Motif-index of folk literature (1955-1958). ... In his introduction, the author explains the concept of the motif as a basis for cataloging. ... The present work is an attempt to survey thoroughly the totality of Polynesian oral tradition and to indicate the distribution and relationships of narrative materials."--Back cover